Parentokracja i konstruowanie nierówności edukacyjno-społecznych - Sobczak, Anna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2018)
The aim of the article is to try to explain what is the ideology of parentocracy and describe its impact on the educational and social functioning of individuals, in particular in the conditions of modern mass education, also at the academic level. In this paper the method of analysis and synthesis of literature sources was used. Three possible ways of thinking about parentocracy can be distinguished, which include choices made by parents regarding their children’s participation in the education process, socialization in the family and the “post-educational” period associated with the entry of graduates into the labour market, in which parents’ social capital plays a significant role. Currently one of the important sources of educational and social inequality is the family, and more specifically parents and their resources, which they can use to ensure a proper education for their children.
Keywords: family; education; children; parentocracy; social inequalities